Discourse, Narrative, and Voice: The Power of Communicating Bioethics Through the Media - Hortense Gallois (Canadian Journal of Bioethics, 2024)
This perspective explores the role of the bioethicist in shaping public discourse through the media, while accounting for the power of narratives and voice.